The effectiveness of evidence-based medicine workshop as a method for disseminating a clinical practice guideline on hypertension - Espallardo, Noel
Theses--(Master in Science in Epidemiology-Clinical Epidemiology) UPCM
A recent study showed that the most common reasons for developing a clinical practice guideline is to improve the quality of care. Benefits however, do not usually follow. Despite the presence of a clinical practice guideline on the diagnosis and management of ypertension (JNC V), conformance to the recommendation that beta blockers and diuretics are the first drug of choice is only about 60%. This study was designed to determine the effectiveness of two methods of disseminating a clinical practice guideline: evidence based medicine workshop vs. didactic lecture on the clinical practice guideline in terms of knowledge about the diagnosis and treatment of hypertension and appropriateness of care such as history taking, physical examination, laboratory work up, non-pharmacologic and pharmacologic treatment for patients with hypertension. This study was a single blind randomized controlled trial. The medical interns were randomized by groups based on their batch rotation in the Department of Family and Community Medicine at the Philippine General Hospital into the two interventions, evidence-bsed medicine workshop and didactic lecture. Their knowledge on the diagnosis and treatment of hypertension were evaluated by a written examination before and after the intervention. History taking, physical examination skills and prescribing practice were evaluated by doing a chart review before and after the intervention. Evaluators were blinded to the group where the medical intern was randomized. The study was conducted in the Department of Family nd Community Medicine of the Philippine General Hospital. The hospital is a tertiary care center affiliated with the University of the Philippines College of Medicine. One group participated in an evidence-based medicine workshop on the clinical practice guideline for the diagnosis and treatment of hypertension. This workshop involved critical appraisal of the clinical practice guideline and the articles used by the guideline in their recommendtions. The other group received a didactic lecture on the recommendations of the clinical practice guideline for the treatment of hypertension. A total of 162 medical interns were included in the study. Eighty-four were randomzied to the didactic lecture group while seventy-eight were randomized to the EBM workshop group. The demographic characteristics were not significantly different between the two groups. In terms of knowledge, both groups showed a significant increase in knowledge score after the intervention with a higher increase noted in the EBM workshop group. The improvement was 12.1% (95% CI; 8.6-15.7) in the EBM group and 9.2% CI; 6.5 - 12.0) in the lecture group. The history taking and physical examination skills significantly improved after the intervention in the EBM group but not in the lecture group. The improvement in the EBM group was 10.7%(95% CI; 5.7 - 15.7) for history taking and 8.7% (95% CI; 5.7 - 11.9) in the physical examination skills while in the didactic lecture the improvement was only 1.0% (95% CI; -4.8 - 6.9) in history taking skills and 0.7% (95% CI; -3.11 - 4.6) in physical examination skills. In terms of nonpharmacologic treatment, the improvement was also significant in the EBM group with 32.8% (95% CI; 20-4-45.3) but not in the lecture group with 1.1% (95% CI; 8.2 - 10.4). The improvement in the diagnostic skills and appropriateness of pharmacologic treatment was not statistically significant between the two groups. In terms of appropriateness of care, the EBM group significantly provided more appropriate care than the lecture group in terms of history taking (OR=3.2; 95% CI; 1.1-9.0), phyical examination (OR=5.6; 95% CI: 1.3-23.9) and nonpharmacologic treatment (OR=8.0; 95% CI: 3.9-16.2). The difference in the appropriateness of care was not significant in terms of diagnostic testing and pharmacologic intervention. The study showed a higherr increase in knowledge, history taking, physical examination and non-pharmacologic treatment skills of medical interns in the EBM workshop group than in the didactic lecture group but no significant difference in increase was noted in the appropriateness of treatment and laboratory diagnosis. This study showed that EBM workshop may be a better way of disseminating a clinical practice guideline for hypertension than plain didactic lecture. The mixed effect on the different outcomes needs further investigation.
Keywords: Hypertension; Evidence-based medicine